匿名使用者
匿名使用者 發問時間: 電腦與網際網路程式設計 · 1 0 年前

求 f(x)=tanhx 之反函數

y(x)=tanhx 之反函數 x=1/2 ln (1+y)/(1-y)

f(x)=(x^2+1)^(1/2) g(x)=tanx的合成函數 f(g(x)) = |secx|

求過程

謝謝

1 個解答

評分
  • 1 0 年前
    最佳解答

    sinhx=(e^x-e^-x)/2,coshx=(e^x+e^-x)/2,tanhx=sinhx/coshx=(e^x-e^-x)/e^x+e^-x)y(x)=tanhx,y'(x)=sec^2hx=1/cos^2hx=4/(e^x+e^-x)^2≠0,對於所有x故其反函數存在,令y=(e^x-e^-x)/(e^x+e^-x)=>ye^x+ye^-x=e^x-e^-x=>(y+1)e^-x=(1-y)e^x=>y+1=(1-y)e^2x=>e^2x=(1+y)/(1-y),兩邊取ln=>2x=ln(1+y)/(1-y)=>x=1/2ln(1+y)/(1-y)f(x)=(x^2+1)^1/2,將g(x)=tanx代入,f(g(x))=(1+tan^2x)^1/2=(sec^2x)^1/2=|secx|

    參考資料: me
還有問題?馬上發問,尋求解答。